Electroacupuncture alleviates diesel exhaust particles-induced inflammatory response in lung through dopamine inhibition of NLRP3 signaling pathway - Yuanting Xie; Jing Han; Qianfeng Wang; Xinyi Fang; Bin Pan; Dongyang Han; Jingyu Li; Wenpu Shao; Xiaoqing Hong; Wenyue Tu; Wenye Geng; Weihua Li; et al. (Ecotoxicology and Environmental Safety)
Fine particulate matter (PM2.5) remains a major environmental problem both in China and worldwide. Extensive researches have indicated that PM2.5 exposure can lead to various adverse health effects through pulmonary and systemic inflammation, making it crucial to explore effective individual intervention strategies. Electroacupuncture, an ancient Chinese medical treatment, has been proven safe and effective for treating some diseases, however, its potential in preventing PM2.5-induced toxicity remains unclear. This study aimed to explore the potential of electroacupuncture in mitigating pulmonary inflammation induced by diesel exhaust particles (DEP). Electroacupuncture was administered 15 minutes before intratracheal instillation of DEP, and the results showed that it markedly reduced DEP-induced pulmonary inflammation, as evidenced by significantly decreased pro-inflammatory markers at both gene and protein levels in lung, via regulating the macrophage polarization. Further analysis indicated that electroacupuncture promoted the production and release of dopamine from the adrenal medulla of mice, which then translocated to lung via circulation and inhibited the pulmonary NLRP3/caspase-1 signaling pathway. In addition, the time effectiveness experiment suggested that the anti-inflammatory effect of electroacupuncture against DEP can last for 48 hours. These findings suggest that electroacupuncture holds potential as a therapeutic intervention for health issues caused by PM2.5 exposure.